Análisis de cumplimiento tributario con los organismos de control de la empresa Lojasystem C.A “KLIX” de la ciudad de Loja, períodos 2020-2021. - Vega Tandazo, Lady Silvana (2023)
The present work called ANALYSIS OF TAX COMPLIANCE WITH THE CONTROL ORGANIZATIONS OF THE COMPANY LOJASYSTEM C.A "KLIX" OF THE CITY OF LOJA, PERIODS 2020-2021, was elaborated with the purpose of analyzing and verifying the adequate compliance of the tax obligations of the company in order to provide important information to the owner of the company. Its importance is focused on the development of the specific objectives set, to fulfill the first objective, a diagnosis was made about the tax, labor and corporate obligations with the Internal Revenue Service (SRI), based on the interview with the manager and accountant of the entity, in this way a prior knowledge was obtained about how informed the company is about these obligations; for the execution of the second objective, the Tax Compliance Report was made by means of the Annexes stipulated in the periods 2020-2021, these annexes are divided into three important parts: part one: General Annexes which contains informative data of the company, follow-up of the tax aspects and of the computerized accounting system; in the second part are the Annexes related to Income Tax and finally in part three we find the Annexes of other taxes, specific revisions and economic sectors. With the data reflected in the accounting records and in the declarations of the respective company forms, the information reported to the Internal Revenue Service was verified. Finally, a report was prepared containing the analysis of the annexes included in the Tax Compliance Report (ICT), as well as recommendations and conclusions based on the results. At the conclusion of this work, the positive aspects of performing a tax compliance analysis were evidenced, since through it the efficiency of the tax procedures was evaluated, which established accurate information on the differences located, in this way will allow informing the owner of the results obtained when performing the analysis in the company, in this way a proper tax culture that contributes to the benefit and development of the country will be promoted.